Effects of light addition and water inlet spray on growth rates and agar yields of the red seaweed Gracilaria cornea grown in a land based maricultural system - Shauli, Lilach; Salomon, Eitan (Frontiers in Marine Science, 2025)
The red seaweed genus Gracilaria is an important source for agar extraction. Gracilaria seaweeds are mostly wild-harvested or commercially cultivated in offshore systems, exposed to fluctuating biotic and abiotic conditions which may affect their growth rates and agar yields. Land-based systems allow for better control over the cultivation conditions but at high infrastructure and operational costs. Here we show that addition of artificial illumination throughout the ambient light period up to 14 hours significantly increased the growth rates of this seaweed. However, adding 4 hours of artificial illumination to an ambient 10-hour light period, for a total of 14 hours did not increase growth rates of Gracilaria cornea grown in a land-based tank system. In addition, we introduced a water inlet spray system that created water turbulence in the growth tanks without the need for a costly air bubbling system. G. cornea grown using the water spray system grew in rates comparable to those grown aided by air bubbling. High quality agar was extracted from the seaweeds. Agar yields were similar in the light addition and the water spray experiments as compared to the controls and remained at values between 14-20% on a dry weight basis. We suggest that artificial light addition should be considered for use in land-based system, even during daytime, after a suitable cost-benefit analysis has been made. We also recommend the use of the water spray method as the preferred low-cost option for maintaining sufficient water turbulence in Gracilaria growth tanks.